2016
DOI: 10.1002/tcr.201500269
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly Active Chiral Titanium Catalysts for the Enantioselective Addition of Various Organometallic Reagents to Aldehydes

Abstract: The catalytic enantioselective carbonyl addition reaction has long attracted the interest of chemists because of its synthetic importance. Although many highly enantioselective reactions have been developed, with few exceptions the reactions are carried out at relatively high catalyst loadings, making them less practical for scale-up applications. In addition, organometallic reagents employed as carbon nucleophiles have been limited to those with relatively low reactivity, such as diorganozincs and arylboronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 134 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…In these reactions, 3,3'-disubstituted BINOL-derived phosphorica cids 1 (Figure 1) are mostf requently used for highly enantioselective reactions.O nt he other hand, 3-monosubstitutedB INOL-derived phosphoric acids 2 are less frequently used as catalysts [4] and, to the best of our knowledge,s imple 3-monosubstituted BINOL-derived phosphoric acidsw ithout any polar functionalitieso nt he 3-sub-stituenth ave not been used in highly enantioselective reactions. This fact is surprising because the parent 3-monosubstituted BINOL derivatives [5] and their phosphoramidite analogues [6] are good ligands for several catalytic enantioselective reactions. Herein, we report that simple 3-mono-substituted chiral BINOL-phosphoric acids are even more selective organocatalysts than 3,3'-disubstituted analogsi nd irect enantioselective Friedel-Crafts-type alkylation of N-unprotected a-ketiminoester.T he origin of the observed high enantioselectivity with the 3-monosubstituted catalyst is also discussed.This work emerged from our recent focus on the utility of Nunprotected ketimines in direct catalytic nucleophilica ddition reactions.…”
mentioning
confidence: 99%
“…In these reactions, 3,3'-disubstituted BINOL-derived phosphorica cids 1 (Figure 1) are mostf requently used for highly enantioselective reactions.O nt he other hand, 3-monosubstitutedB INOL-derived phosphoric acids 2 are less frequently used as catalysts [4] and, to the best of our knowledge,s imple 3-monosubstituted BINOL-derived phosphoric acidsw ithout any polar functionalitieso nt he 3-sub-stituenth ave not been used in highly enantioselective reactions. This fact is surprising because the parent 3-monosubstituted BINOL derivatives [5] and their phosphoramidite analogues [6] are good ligands for several catalytic enantioselective reactions. Herein, we report that simple 3-mono-substituted chiral BINOL-phosphoric acids are even more selective organocatalysts than 3,3'-disubstituted analogsi nd irect enantioselective Friedel-Crafts-type alkylation of N-unprotected a-ketiminoester.T he origin of the observed high enantioselectivity with the 3-monosubstituted catalyst is also discussed.This work emerged from our recent focus on the utility of Nunprotected ketimines in direct catalytic nucleophilica ddition reactions.…”
mentioning
confidence: 99%
“…1 These alcohols are key compounds serving as both starting materials and resolving agents, which are used in the preparation of pharmaceuticals or intermediates. 1,2…”
Section: Introductionmentioning
confidence: 99%
“…Because of greatly reactive, however, the catalytic asymmetric addition of Grignard reagents to aldehydes is typically challenging . Only recently successful strategies were developed in access to highly enantiopure secondary alcohols via catalytic asymmetric Grignard reactions . The groups of Harada, Xu, and Yus utilized superstoichiometric Ti (O i ‐Pr) 4 to transmetallate RMgX (Br, Cl) to less reactive R‐Ti (O i ‐Pr) 3 , and then R‐Ti (O i ‐Pr) 3 highly enantioselectively delivered R group to aldehydes catalyzed by chiral diol‐Ti (O i ‐Pr) 2 complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Only recently successful strategies were developed in access to highly enantiopure secondary alcohols via catalytic asymmetric Grignard reactions. [11][12][13] The groups of Harada, [14][15][16] Xu, 17,18 and Yus 19,20 utilized superstoichiometric Ti (Oi-Pr) 4 to transmetallate RMgX (Br, Cl) to less reactive R-Ti (Oi-Pr) 3 , and then R-Ti (Oi-Pr) 3 highly enantioselectively delivered R group to aldehydes catalyzed by chiral diol-Ti (Oi-Pr) 2 complexes. Our group demonstrated that the additive bis([2-[N,N′-dimethylamino)]thyl) ether (BDMAEE) effectively deactivated the reactivity of Grignard reagents and then similarly transmetallated R functional group of RMgBr to R-Ti (Oi-Pr) 3 by using stoichiometric Ti (Oi-Pr) 4 .…”
Section: Introductionmentioning
confidence: 99%